2015
DOI: 10.2214/ajr.14.13354
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Ultrasound in Female Patients With Nipple Discharge

Abstract: For females presenting with pathologic nipple discharge, ultrasound is a useful diagnostic tool and may be worth including in the routine evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 19 publications
0
62
1
Order By: Relevance
“…Ashfaq et al and Bahl et al emphasized the variability across institutions and no solid data in the clinical or radiological information to distinguish malignant lesions from benign etiology . Ashfaq et al, concluded evidence‐based evaluation and treatment algorithm for patients can stratify patients into low‐risk and high‐risk categories and that low‐risk patients can be safely followed clinically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ashfaq et al and Bahl et al emphasized the variability across institutions and no solid data in the clinical or radiological information to distinguish malignant lesions from benign etiology . Ashfaq et al, concluded evidence‐based evaluation and treatment algorithm for patients can stratify patients into low‐risk and high‐risk categories and that low‐risk patients can be safely followed clinically.…”
Section: Discussionmentioning
confidence: 99%
“…institutions and no solid data in the clinical or radiological information to distinguish malignant lesions from benign etiology. 18,19 Ashfaq et al, concluded evidence-based evaluation and treatment algorithm for patients can stratify patients into lowrisk and high-risk categories and that low-risk patients can be safely followed clinically. Our study reconfirms the variability in patient management in management of nipple discharge and given the low rate of malignancy in low-risk patients (defined as ones undergoing negative noninvasive imaging) that emphasis should be made to streamline a more patient-focused management based on risk stratification.…”
Section: Ashfaq Et Al and Bahl Et Al Emphasized The Variability Acrossmentioning
confidence: 99%
“…The most common cause of pathologic nipple discharge is an intraductal neoplastic lesion (ie, papilloma or papillomatosis, accounting for 35%‐56% of cases), followed by secretory breast disease such as plasma cell mastitis with duct ectasia (17%‐36%) and fibrocystic change . Cancer is a less common etiology, ranging from 5% to 23% in patients presenting with pathologic nipple discharge in single institution studies . The most common type of cancer that presents with pathologic nipple discharge is ductal carcinoma in situ (DCIS)…”
Section: Introductionmentioning
confidence: 99%
“…According to the American College of Radiology's (ACR) Appropriateness Criteria, diagnostic mammography is the standard initial step in evaluating pathologic nipple discharge in patients 30 years of age or older . Since mammography has a low sensitivity (7%‐10%) for the detection of malignancy in this setting, ultrasound complements diagnostic evaluation by allowing for detailed evaluation of the sub‐areolar ducts and providing guidance for subsequent needle biopsy, if needed . In the setting of a negative mammogram and ultrasound, ductography or dynamic contrast‐enhanced (DCE) magnetic resonance imaging (MRI) may be performed to further evaluate the etiology of pathologic nipple discharge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation